2020
DOI: 10.1016/j.hroo.2020.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation detection from raw photoplethysmography waveforms: A deep learning application

Abstract: BACKGROUND Atrial fibrillation (AF), a common cause of stroke, often is asymptomatic. Smartphones and smartwatches can detect AF using heart rate patterns inferred using photoplethysmography (PPG); however, enhanced accuracy is required to reduce false positives in screening populations. OBJECTIVE The purpose of this study was to test the hypothesis that a deep learning algorithm given raw, smartwatch-derived PPG waveforms would discriminate AF from normal sinus rhythm better than algorithms using heart rate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Indeed, we have shown that detecting PAC/PVC can lead to significant false positive reduction during AF detection [ 40 ]. Other recent published reports [ 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] have largely focused on AF without accounting for PAC/PVC and consequently their accuracy of AF detection was suboptimal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we have shown that detecting PAC/PVC can lead to significant false positive reduction during AF detection [ 40 ]. Other recent published reports [ 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] have largely focused on AF without accounting for PAC/PVC and consequently their accuracy of AF detection was suboptimal.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the dataset used in this paper did not consider PVC arrhythmia. Many other studies on AF detection using wrist PPG sensors were conducted [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], however, none of them considered PAC or PVC case in their AF detection.…”
Section: Introductionmentioning
confidence: 99%
“…The properties have higher levels of agreement/equivalence when the PPG signals are not excessively situated with motion artifacts. Various predictive and detection models have been implemented using different HRV metrics with standard statistical and machine learning approaches [14][15][16][17][18][19]. However, there are considerably fewer deep learning-based models oriented towards usage in smartphones and wearable devices.…”
Section: Introductionmentioning
confidence: 99%
“…Photoplethysmography (PPG) with pulse waveforms generated from optical sensors of mobile devices has become a new trend and shows sufficient accuracy for the detection of heart rate and other physiological parameters 13 . Recent studies revealed various algorithms with good performance in discriminating AF from sinus rhythm 14 17 . Though digital wearables are increasingly popular worldwide, most elderly, who are the main population of AF, are still not used to the application of this high-tech device 18 .…”
Section: Introductionmentioning
confidence: 99%